A Finite-state Machine Based Approach for Fault Detection and Classification in Transmission Lines. Issue 1 (2nd January 2016) - Yadav, Anamika; Swetapadma, Aleena
Abstract: In this article, a novel protective relaying scheme based on a finite-state machine is proposed to detect fault in transmission lines, classify the fault, and identify the faulty phase. The three-phase fundamental component of current and the zero-sequence current signals measured at one end of the double-circuit line are used as inputs. The finite-state machine based relaying scheme relies on time-series analysis of current signals only and is built upon the concepts from the finite-state automata theory. The finite-state machine works by transition of one state to another by following certain conditions. The proposed relay is tested during different shunt faults—inter-circuit and cross-country faults—with wide variations in fault parameters. The proposed method is adaptive to variation in fault type, fault resistance, fault inception angle, fault location, power flow angle, different line length, transient faults, current transformer (CT) saturation, and no-fault events. The relay performed correctly for 99.9% of test cases, proving the effectiveness of the proposed method. Furthermore, the proposed method can provide faster, more reliable protection against all shunt faults, inter-circuit and cross-country faults, with wide variations in parameters, and the protection range is effectively extended and greatly improved, which contributes to system safety and stability.